2012
DOI: 10.1103/physrevb.86.054437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dilution and steric effects in the multiferroic delafossite CuCrO2

Abstract: In order to get to the bottom of substitution effects reported in CuCrO 2 delafossite, structural, magnetic, and electric properties of several CuCr 1−x M x O 2 series, where M 3+ is a S = 0 cation (M 3+ = Al 3+ , Ga 3+ , Sc 3+ , Rh 3+ ), have been investigated. It is shown that the homogeneity of the substitution is element dependent and is particularly difficult to achieve for the smallest Al 3+ cation. Ferroelectricity and dielectric properties are found to depend on the x value, but also on the nature of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
3
16
1
Order By: Relevance
“…Such an increase in M B leads to a decrease in |θ CW |, as shown in Fig. 14, which displays very good agreement with the experimental observations [45]. It is worth noting that for x = 0.3, the M B behavior is still far from that of the ideal paramagnet ( Fig.…”
Section: Magnetic Properties Under a Small Applied Magnetic Fieldsupporting
confidence: 86%
See 3 more Smart Citations
“…Such an increase in M B leads to a decrease in |θ CW |, as shown in Fig. 14, which displays very good agreement with the experimental observations [45]. It is worth noting that for x = 0.3, the M B behavior is still far from that of the ideal paramagnet ( Fig.…”
Section: Magnetic Properties Under a Small Applied Magnetic Fieldsupporting
confidence: 86%
“…On the other hand, it was shown that Ga 3+ directly affects the antiferromagnetic nature of the compound, leading to the possibility of a spin glass behavior [46]. Moreover, neutron powder diffraction experiments performed on CuCr 0.9 Ga 0.1 O 2 showed that the magnetic peaks observed at 1.8 K correspond to a propagation vector q = (0.329, 0.329, 0) where they are significantly broadened compared to that of CuCrO 2 , which evidences a disorder in the magnetic configuration [45]. Nevertheless, magnetoelectric properties of CuCr 1−x Ga x O 2 are still rarely studied, and therefore, complementary investigations are necessary for better understanding of these materials.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to neutron powder diffraction data, magnetic susceptibility measurements, electrical permittivity and electrical polarization data of magnetically diluted CuCr 1−x M x O 2 with M = Al, Ga, Sc, Rh by Pachoud et al the magnetic ground state turned out to be very robust against removal of Cr [95]. These authors thus concluded that the magnetic ground state of CuCrO 2 is very different from that of CuFeO 2 .…”
Section: Cucromentioning
confidence: 99%